2016
DOI: 10.1016/j.jmb.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bni5 Binding on Septin Filament Organization

Abstract: Septins are a protein family found in all eukaryotes (except higher plants) that have roles in membrane remodeling, formation of diffusion barriers, and as a scaffold to recruit other proteins. In budding yeast, proper execution of cytokinesis and cell division requires formation of a collar of circumferential filaments at the bud neck. These filaments are assembled from apolar septin hetero-octamers. Currently, little is known about the mechanisms that control the arrangement and dynamics of septin structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…Right , depiction of Cdc11-capped rods forming paired filaments in either low salt (<75 mM) ( Bertin et al, 2008 ) or on the surface of PIP2-containing lipid monolayers ( Bertin et al, 2010 ; Bridges et al, 2014 ); dashed box indicates zoomed in inset shown to the right. (C) Left , depiction of two Bni5 proteins (red molecules) interacting with Cdc11-CTEs found in paired septin filaments to lower the average interfilament distance to 10 nm ( Finnigan et al, 2015 ; Booth et al, 2016 ). Right , depiction of Bni5 bundling septin filaments into large clusters in vitro in a dose-dependent manner ( Patasi et al, 2015 ).…”
Section: Transforming the Nascent Septin Ring Into A Septin Hourglassmentioning
confidence: 99%
See 3 more Smart Citations
“…Right , depiction of Cdc11-capped rods forming paired filaments in either low salt (<75 mM) ( Bertin et al, 2008 ) or on the surface of PIP2-containing lipid monolayers ( Bertin et al, 2010 ; Bridges et al, 2014 ); dashed box indicates zoomed in inset shown to the right. (C) Left , depiction of two Bni5 proteins (red molecules) interacting with Cdc11-CTEs found in paired septin filaments to lower the average interfilament distance to 10 nm ( Finnigan et al, 2015 ; Booth et al, 2016 ). Right , depiction of Bni5 bundling septin filaments into large clusters in vitro in a dose-dependent manner ( Patasi et al, 2015 ).…”
Section: Transforming the Nascent Septin Ring Into A Septin Hourglassmentioning
confidence: 99%
“…One such SAP, Bni5, localizes to the bud neck in a septin-dependent manner ( Lee et al, 2002 ). Bni5 appears to interact with the CTEs of the terminal subunits Cdc11 and Shs1 in vitro and in vivo ( Figure 1C ) ( Finnigan et al, 2015 ; Booth et al, 2016 ). Recombinant Bni5 can reduce the distance between individual filaments of a paired filament and can also bundle septin filaments, thereby contributing to a higher-order organization ( Figures 1B,C ) ( Patasi et al, 2015 ; Booth et al, 2016 ).…”
Section: Transforming the Nascent Septin Ring Into A Septin Hourglassmentioning
confidence: 99%
See 2 more Smart Citations
“…Bni5 is essential for the localization of Myo1, the sole heavy chain of myosin-II in budding yeast, to the bud neck prior to cytokinesis by serving as a linker between the septins and the tail region of Myo1 (Fang et al 2010; Finnigan et al 2015). Bni5 dimerizes and regulates the spacing and organization of paired septin filaments by directly interacting with the terminal subunit Cdc11 (Patasi et al 2015; Booth et al 2016). Thus, Bni5 is thought to play a key role in stabilizing the septin hourglass.…”
Section: Regulating the Varieties Of Septin Structuresmentioning
confidence: 99%